5(2x-3)=7+4(x-1)

Simple and best practice solution for 5(2x-3)=7+4(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-3)=7+4(x-1) equation:


Simplifying
5(2x + -3) = 7 + 4(x + -1)

Reorder the terms:
5(-3 + 2x) = 7 + 4(x + -1)
(-3 * 5 + 2x * 5) = 7 + 4(x + -1)
(-15 + 10x) = 7 + 4(x + -1)

Reorder the terms:
-15 + 10x = 7 + 4(-1 + x)
-15 + 10x = 7 + (-1 * 4 + x * 4)
-15 + 10x = 7 + (-4 + 4x)

Combine like terms: 7 + -4 = 3
-15 + 10x = 3 + 4x

Solving
-15 + 10x = 3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-15 + 10x + -4x = 3 + 4x + -4x

Combine like terms: 10x + -4x = 6x
-15 + 6x = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
-15 + 6x = 3 + 0
-15 + 6x = 3

Add '15' to each side of the equation.
-15 + 15 + 6x = 3 + 15

Combine like terms: -15 + 15 = 0
0 + 6x = 3 + 15
6x = 3 + 15

Combine like terms: 3 + 15 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 9(x+2)=5x+17 | | -2x-5+7x=50 | | 4(w-2)+2(3w+1)=44 | | 9x-2+40=20+5 | | 8x=5x-18 | | 10x-3x+7= | | 3x+17=4x+7 | | 3(v-4)=9+2v | | y^2+yx-x^2-4x=-9 | | 4+x+7x=100 | | 59.9=125+6x | | -1+(Vu+11)=7 | | 7x+3=2x+10 | | -3y+8=-3y-8 | | 7x-4=-67 | | 7x-y=59 | | 3x+3=x+19 | | 7a-5=b | | 9x+3=2(4x-3)+9 | | 5-9=-12 | | -9-3y=27 | | 9-4x=29 | | 18=2z-2 | | x^4+7x^2=8 | | 11-(2v+4)=2v-7 | | -3x=-1.5 | | 8w-4w=20 | | 6x+9=2x-7 | | x^2=-24+108x | | 18=2z-12 | | 2b+9= | | x^3-2x^2-6x-3=0 |

Equations solver categories